Capital controls in Brazil: effective? - Marcos Chamon; Márcio Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2013)
We analyze the impact of the controls and restrictions on capital inflows that Brazil has adopted since late 2009. We document that these measures had some success in segmenting the Brazilian and global financial markets, as measured by wedges between onshore and offshore prices of similar fixed and variable income assets. However, that failed to translate into significant changes in the exchange rate, at least in the immediate aftermath of these measures, suggesting limited success in mitigating real appreciation. But capital controls/restrictions may have contributed to the sizable depreciation of the real in 2012, possibly amplifying the effect on the exchange rate of cuts in the interest policy rate during that period.
Keywords: F31; F32; F36; F65; 330; Kapitalverkehrskontrolle; Brasilien